Noonan syndrome: genetic and clinical update and treatment options - Atilano Carcavilla; Larisa Suárez-Ortega; Amparo Rodríguez Sánchez; Isabel Gonzalez-Casado; Marta Ramón-Krauel; Jose Ignacio Labarta; Sofia Quinteiro Gonzalez; Isolina Riaño Galán; Juan Pedro López-Siguero (Elsevier, 2020)
Noonan syndrome (NS) is a relatively common genetic condition characterised by short stature, congenital heart defects, and distinctive facial features.NS and other clinically overlapping conditions such as NS with multiple lentigines (formerly called "LEOPARD" syndrome), cardiofaciocutaneous syndrome, or Costello syndrome, are caused by mutations in genes encoding proteins of the RAS-MAPKinases pathway. Because of this shared mechanism, these conditions have been collectively termed "RASopathies". Despite the recent advances in molecular genetics, nearly 20% of patients still lack a genetic cause, and diagnosis is still made mainly on clinical grounds.NS is a clinically and genetically heterogeneous condition, with variable expressivity and a changing phenotype with age, and affects multiple organs and systems. Therefore, it is essential that physicians involved in the care of these patients are familiarised with their manifestations and the management recommendations, including management of growth and development. Data on growth hormone treatment efficacy are sparse, and show a modest response in height gains, similar to that observed in Turner syndrome.The role of RAS/MAPK hyper-activation in the pathophysiology of this group of disorders offers a unique opportunity for the development of targeted approaches. Resumen: El síndrome de Noonan (SN) es una enfermedad de origen genético relativamente frecuente cuyas manifestaciones fundamentales son la talla baja, la cardiopatía congénita y un fenotipo facial característico.La causa del síndrome de Noonan y de otras enfermedades clínicamente solapadas como el síndrome de Noonan con lentiginosis múltiple (anteriormente llamado síndrome LEOPARD), el cardiofaciocutáneo o el síndrome de Costello, son mutaciones en genes que codifican para proteínas de la vía de señalización de las RAS-MAPKinasas. Debido a este sustrato común este grupo de enfermedades son denominadas colectivamente "rasopatías". A pesar de los avances genéticos de las últimas décadas cerca de un 20% de pacientes no tienen causa genética identificada, y el diagnóstico sigue siendo clínico.El síndrome de Noonan se caracteriza por una alta heterogeneidad clínica y genética, con afectación variable, y cambiante con la edad, de múltiples órganos y sistemas. Debido a esta variabilidad es fundamental que los médicos involucrados en su cuidado estén familiarizados con sus manifestaciones y conozcan las recomendaciones de seguimiento, incluido el seguimiento del crecimiento y desarrollo. Hasta la fecha los escasos datos de crecimiento con GH a talla adulta dan resultados de ganancia de talla moderados, semejantes a los obtenidos en síndrome de Turner.La hiperactivación de la vía RAS-MAPK como base común de esta familia de enfermedades brinda una oportunidad única para el desarrollo de tratamientos dirigidos a la etiología de estos trastornos.